Awareness of Livestock Farmers on ICT tools - Devi, Letha (Journal of Extension Education, 2020)
A study was conducted to assess farmer capability, awareness and preparedness about ICT tools for livestock farming. The data were collected from 60 respondents of Karnataka, India regarding awareness about ICT tools. The results indicate that 100 per cent of the farmers were aware about various ICT tools and media such as TV, websites, Mobile Applications, SMS based services, Kisan Call Centres etc. All the respondents had knowledge about how to use SMS based services, whereas 97 percent of them knew about use of Mobile applications. Many of them did not know about how to use websites.